Darkness unleashed - Ivy, Alexandra (New York : Kensington Pub., 2009)
A scarred recluse, Jagr makes no secret of his disdain for others' company. But now, as a member of Chicago's powerful vampire clan, he has certain obligations to fulfill. The latest: track down a missing were-pureblood and return her to her sister. The problem: Regan Garrett has no intention of complying.
Keywords: Vampires -- Fiction; Paranormal romance stories; Romantic suspense fiction